Gitelman's Syndrome: An unusual cause of Recurrent Attack of Quadriparesis (Journal of Medicine, 2015)
Gitelman'?s syndrome, discovered in 1966 by Gittleman,Graham and Welt, is an autosomal recessive renal tubular disorder and characterized by hypokalemic metabolic alkalosis, hypomagnesaemia, hypocalciuria. This is a rare cause of hypokalemia which has an autosomal recessive inheritance. Here we are reporting a case of a 35 years old lady presented with recurrent attacks of quadriparesis due to hypokalemia and pain in multiple joints. Later we diagnosed the case as Gitelman?'s syndrome.DOI: http://dx.doi.org/10.3329/jom.v16i1.22407 J MEDICINE 2015; 16 : 59-60